2021
DOI: 10.1007/s42452-021-04757-4
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent control of induction motor for photovoltaic water pumping system

Abstract: This work aims to improve the performance of direct torque control (DTC) technique for induction motor based photovoltaic (PV) water pumping system (PVWPS). The innovative aspect of this work consists in introducing the adaptive fuzzy logic control and the fuzzy logic control techniques as alternative approaches to conventional DTC to control the PVWPS. To ensure a good operation of the PV array, a variable step size incremental conductance (VSS INC) is implemented. Simulation studies of the proposed topology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…The induction motor stator and rotor voltage are obtained in a synchronously rotating reference frame using the electromagnetic Equations ( 6) and ( 7) [16]:…”
Section: Induction Motor Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The induction motor stator and rotor voltage are obtained in a synchronously rotating reference frame using the electromagnetic Equations ( 6) and ( 7) [16]:…”
Section: Induction Motor Modelmentioning
confidence: 99%
“…To the q-axis PI current regulator is added in cascade, a speed controller, that becomes the main loop. The speed controller provides the reference for the inner loop q-axis current (i qs * ) containing the current regulation (q-axis) from the electromechanical torque according to Equation ( 12) from [16], resulting in Equation (29):…”
Section: Classical Variable Speed Pump Control Strategy Implemented I...mentioning
confidence: 99%
“…Tis optimization defnes a cost function that values the behavior of the fuzzy dynamic system, considering the control deviation and its variation. Equation (22) shows the cost function, whose minimization guarantees the achievement of the setpoint under the condition of minimum stress of the system or actuators.…”
Section: Mamdani-type Fuzzy Inference System Processingmentioning
confidence: 99%
“…Cross and Ma compared diferent techniques for model-based condition monitoring systems applied in wind turbines, such as linear model, artifcial neural networks, state-dependent "pseudo" transfer function, and Mamdani fuzzy-based approach, where this last technique demonstrated to be practically feasible to be implemented [21]. Errouha et al introduce the Mamdani fuzzy logic techniques as an alternative approach to conventional direct torque control (DTC) to control induction motors for water pumping systems, where the results showed that the fuzzy control could improve the performance by minimizing the fux and torque ripples, reducing overshoot and undershoot, and enhancing the response time [22].…”
Section: Introductionmentioning
confidence: 99%
“…However, there are important drawbacks: the torque and stator flux ripples have a large amplitude, specially at low speeds and the switching frequency is very variable [10]. Errouha et al [11] designed fuzzy logic blocks have taken the place of lookup tables and hysteresis controllers when employing adaptive fuzzy logic control for speed regulation to avoid these drawbacks. As a result, the flux and torque ripples are reduced to a minimum.…”
Section: Introductionmentioning
confidence: 99%